A model of the decision making on the basis of ratios profitability and leverage - Azami, Bahareh; Izadinia, Naser; Zangirani, Daryosh Mohamadi (Ciência e Natura, 2015)
This study presents a model for performance decisions based on the ratios profitability and leverage .Decision Making is whether thecorrelation between the bank’s top 12 banks in the two DEA models and TOPSIS ratios profitability and leverage as well as the top of the 68companies profitability and leverage there, Because recent research has been little attention to this issue. The purpose of this study, appliedthe analytical descriptive method After tests results showed that the top bank in terms of performance and top company in terms ofperformance and profitability of all companies with leverage ratios, the correlation was significant at 95% And the resulting ranking ofbanks was the result of the work of other researchers in the last hypothesis, a comprehensive model for all companies based on TOPSISmethod was introduced.